2017
DOI: 10.1016/j.yjmcc.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Serine/Threonine Phosphatases in Atrial Fibrillation

Abstract: Serine/threonine protein phosphatases control dephosphorylation of numerous cardiac proteins, including a variety of ion channels and calcium-handling proteins, thereby providing precise post-translational regulation of cardiac electrophysiology and function. Accordingly, dysfunction of this regulation can contribute to the initiation, maintenance and progression of cardiac arrhythmias. Atrial fibrillation (AF) is the most common heart rhythm disorder and is characterized by electrical, autonomic, calcium-hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 131 publications
(192 reference statements)
0
25
1
Order By: Relevance
“…14 Nevertheless, the majority of studies exploring dysregulation of RyR2 in AF have shown that hyperphosphorylation of RyR2 at residues S2814 and S2808 promotes SR-Ca 2+ leak, spontaneous Ca 2+ -release events, and delayed afterdepolarizations that may underlie arrhythmogenic triggered activity in atrial cardiomyocytes. 21,35,36 Phosphorylation of RyR2 is mediated by PKA and CaMKII, whereas Table II in the online-only Data Supplement), profiling shows comigration of PLN/ SERCA2a and RyR2 in higher-molecular-weight complexes (>1 MDa) and, in addition, JPH2 (≤1 MDa). In contrast, in pAF the RyR2 channel was nearly abolished in higher-molecular-weight complexes, and only monomeric JPH2 exists.…”
Section: Ryr2 Regulation By Pp1 In Afmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Nevertheless, the majority of studies exploring dysregulation of RyR2 in AF have shown that hyperphosphorylation of RyR2 at residues S2814 and S2808 promotes SR-Ca 2+ leak, spontaneous Ca 2+ -release events, and delayed afterdepolarizations that may underlie arrhythmogenic triggered activity in atrial cardiomyocytes. 21,35,36 Phosphorylation of RyR2 is mediated by PKA and CaMKII, whereas Table II in the online-only Data Supplement), profiling shows comigration of PLN/ SERCA2a and RyR2 in higher-molecular-weight complexes (>1 MDa) and, in addition, JPH2 (≤1 MDa). In contrast, in pAF the RyR2 channel was nearly abolished in higher-molecular-weight complexes, and only monomeric JPH2 exists.…”
Section: Ryr2 Regulation By Pp1 In Afmentioning
confidence: 99%
“…However, it is still incompletely understood which RyR2 phosphorylation sites are dephosphorylated by PP1 and protein phosphatase 2A. 21 Chiang et al 22 demonstrated that PP1 R-subunit PPP1R9B (spinophilin) targets PP1c to RyR2. However, genetic ablation of spinophilin in mice reduced PP1c binding to RyR2 by only ≈60%, suggesting that PP1c may bind to the channel through alternative targeting mechanism(s).…”
Section: Ryr2 Regulation By Pp1 In Afmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity, specificity and subcellular localization of the PP2A heterotrimeric holoenzyme complex, are highly regulated through the interaction of regulatory B subunit family members with the substrates [ 6 ]. PP2A contributes to a central role in cardiac diseases [ 7 9 ]. Transgenic mouse lines expressing either mutated structural A subunits or catalytic C subunits exhibit a cardiac phenotype resembling dilated cardiomyopathy [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the single-source, minimalistic philosophy of the approach, there are many factors which play a role in human atrial electrophysiology which have not been included, due to a lack of well characterized and human atrial specific data. For example, the models do not contain detailed descriptions of phosphorylation due to PKA, or the impact of CaMKII (and serine and threonine; Heijman et al, 2014 , 2017 ; Mesubi and Anderson, 2016 ), or additional currents such as small conductance potassium channels ( Skibsbye et al, 2014 ), which may have an important influence on human atrial cell dynamics in control and perturbed conditions. Exclusion of these components is not a claim that they are unimportant, but rather follows from the motivation not to introduce sophistication and complexity by including components which have not been well characterized in the human atria (and specifically the WL) and thus contain potential sources of error, ad hoc parameters, or inaccurately scaled contributions.…”
Section: Discussionmentioning
confidence: 99%